The effect of Resveratrol on the pharmacokinetic profile of tofacitinib and the underlying mechanism. (1st April 2023) - Ye, Zhize; Hu, Jinyu; Wang, Jing; Liu, Ya-nan; Hu, Guo-xin; Xu, Ren-ai
Abstract: The purpose of this study was to (i) investigate the effect of CYP3A4 variants on tofacitinib metabolism, and (ii) investigate the interaction of tofacitinib with resveratrol and its underlying mechanisms. The concentration of M9, the main metabolite of tofacitinib, was determined by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). The results showed that the clearance rate of CYP3A4.18 variant was significantly decreased compared with CYP3A4.1, and the CYP3A4.28 variant was changed, but not statistically significant. In addition, the potential interaction of resveratrol with tofacitinib was determined based on rat liver microsomes (RLM), human liver microsomes (HLM), and CYP3A4 response systems. Resveratrol has an IC50 of 15.67 μM in RLM with a non-competitive mechanism. In HLM with a non-competitive mechanism, the IC50 value was 8.88 μM. The IC50 values were 6.41 μM, 10.60 μM and 27.08 μM in CYP3A4.1, .18 and .28, respectively, all with a competitive mechanism. In the in vivo study, Sprague-Dawley (SD) rats were randomized into two groups (n = 6) to receive tofacitinib with or without resveratrol. We found that the AUC(0-∞) of tofacitinib in the experimental group increased to around 207.5% compared with the control group. And Cmax increased to 260.0%. In summary, our data showed that resveratrol significantly affect the metabolism of tofacitinib, thus providing basic data for the precise clinical application of tofacitinib. Highlights: Three CYP3A4 variants on the metabolism of tofacitinib were investigated. Resveratrol had inhibitory effect on tofacitinib metabolism in RLMs and HLMs. Resveratrol increased the plasma concentration of tofacitinib in rats.